The L-shaped association between body roundness index and all-cause mortality in osteoporotic patients: a cohort study based on NHANES data - Ding, Ziyao; Li, Wenbo; Qi, Haixu; Fang, Tianci; Zhu, Qirui; Qu, Xinzhe; Chen, Changchang; Sun, Jun; Pang, Yong (Frontiers in Nutrition, 2025)
PurposeThis study aims to investigate the relationship between the body roundness index (BRI) and overall mortality rates in individuals with osteoporosis (OP), utilizing information sourced from the NHANES database, in order to assess BRI’s capability as an indicator for predicting mortality risk.MethodsData from NHANES (2005 to 2010, 2013–2014, and 2017–2018) were analyzed, including 1,596 osteoporotic individuals aged 50 and above. BRI was calculated based on waist circumference (WC) and height, categorizing participants into high (>4.07) and low (≤4.07) BRI groups. To analyze the relationship between BRI and mortality while accounting for important covariates, we employed weighted Cox proportional hazards models, conducted Kaplan–Meier survival analyses, and utilized restricted cubic splines (RCS).ResultsHigher BRI was significantly associated with better long-term survival, showing an “L”-shaped nonlinear inverse relationship with mortality, with a threshold at BRI = 5. In subgroup analyses, this association remained relatively stable.ConclusionThe “L”-shaped association between BRI and mortality indicates that BRI may serve as a useful indicator for evaluating mortality risk in patients with OP, thereby informing clinical interventions and public health approaches.